GROWTH AND DEVELOPMENT OF BULLS BORN FROM KOREAN SELECTION BULL SEMENS IN THE CONDITIONS OF UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2024)
The article describes the indicators of feeding, growth and development of bull calves up to 6 months of age, born from highly productive Holstein bulls from South Korea.